Factors influencing in the low level of english active vocabulary in the students of the tenth year of basic education - Tandazo Jaramillo, Alejandra Scarlett (Machala: Universidad Tecnica de Machala, 2016)
this practical work, degree awarded by the ciencias de la educación career, teaching english of the universidad técnica de machala, presents a solution to the following issues raised about the factors that affect the low level of english vocabulary in the students of tenth year of basic education of el oro technical highschool from machala located in the province of el oro, ecuador; academic year 2015-2016.this document presents a detailed resolution which was made of an investigation and a series of application of knowledge gained from experience, so it is sustained on the basis of all the changes that have been making in education system established by la ley orgánica de educación in which reference was made learning standards that aspire to continuous and systematic improvement with regard to the area of english, the new regulation and the scholarship program "go teacher" were granted by the ecuadorian government with the objective that teachers can improve their overall english language and knowledge to teach this language. all these projects have been planned to strengthen language teaching, however, there are several differences that impede progress in the process of learning this language, which is subjected to the student does not attain an adequate level of english. within this project five main factors that allow the development of the language and determine how they influence the learning process thereof will be described. moreover,important that learning a foreign language is easy and this will always be balanced by daily practice.
Keywords: VOCABULARY; TEACHING ENGLISH; TEACHER; STUDENT